"You don't look Puerto Rican": Collective memory and community in Orlando. (October 2016) - Silver, Patricia
Although the 2010 US Census counts documented a large Puerto Rican community in and around Orlando, Florida, 30 years earlier in 1980 Puerto Ricans were living scattered about the area practically unnoticed. A 2008–2009 oral history collection of Puerto Rican memories in Orlando from the 1940s to 1980s gives evidence that middle-class social relations mitigated racial dissonance for some in Orlando's black-white binary, making it possible to almost disappear into the dominant society. This article posits collective memory as a sociocultural process not an outcome and argues that in that almost is a space of dissonance and difference, where strategic moments of forgetting and re-remembering inform the dynamics of collective memory formation. The memories recorded in the collection describe a slippery space between an invisibility emerging from pressures to assimilate and a hypervisibility emerging from US colonial history in Puerto Rico and widespread stereotyping of the Puerto Rican diaspora in the United States.